Toward an Understanding of Best Practices in Student-Athlete Leadership Development Programs: Student-Athlete Perceptions and Gender Differences - Kristina Navarro; Stephen Malvaso (Journal of Applied Sports Management, 2015)
Student-athletes often know how to recognize leadership but struggle to master techniques to exemplify leadership characteristics during their college experience. As Division I athletics now serve as the front porch to American institutions, the visibility of Division I student-athletes has drastically increased. With this visibility comes enhanced responsibility to represent oneself, one's team, and one's university. In turn, it is of heightened interest for higher education and intercollegiate athletics practitioners to understand how to best foster leadership skills for this unique population that garners enhanced media attention. This mixed-method case study considers the perceptions of 221 Division I freshmen student-athletes who completed a formal peer mentorship and leadership development program at a large Southeastern institution. A survey was employed to analyze the relationship between gender and student-athletes' perceived effectiveness of the program's curricular components. Findings displayed no widespread significant impact of gender on perceived effectiveness. Recommendations are presented to enable practitioners nationwide to improve student-athlete leadership development programs considering gender differences and the student-athlete voice.
Keywords: student-athletes; intercollegiate athletics; leadership development